Complete mitochondrial genome of Asiagomphus coreanus (Odonata: Gomphidae), which is endemic to South Korea. Issue 5 (4th May 2022) - Park, Jeong Sun; Kim, Min Jee; Kim, Sung Soo; Kim, Iksoo
Abstract: Asiagomphus coreanus (Doi & Okumura, 1937) belongs to the family Gomphidae in the order Odonata, and has been listed as an endemic species in South Korea. Here, we assembled its complete mitochondrial genome (mitogenome) which is 15, 649 base pairs (bp) in length. The A. coreanus mitogeneome consists of a typical set of genes [13 protein-coding genes (PCGs), 2 ribosomal RNA (rRNA) genes, and 22 transfer RNA (tRNA) genes] and one major non-coding A + T-rich region which is 846 bp long. The gene arrangement of the species was identical to that of commonly found in the majority of the insects. Phylogenetic analyses using the concatenated sequences of 13 PCGs and two rRNA genes of the representative odonate mitogenomes by Bayesian inference method revealed that A. coreanus belongs to the Gomphidae family with a strong nodal support (Bayesian posterior probabilities = 1). Unlike previous phylogenetic analyses (with regards to suborder relationships) the suborder Anisozygoptera—which was represented by a single species, Epiophlebia superstes— was placed as the sister to Zygoptera.